Effect of a low versus intermediate tidal volume strategy on pulmonary complications in patients at risk of acute respiratory distress syndrome—a randomized clinical trial - de Haro, Candelaria; Neto, Ary Serpa; Gomà, Gemma; González, Maria Elena; Ortega, Alfonso; Forteza, Catalina; Frutos-Vivar, Fernando; García, Raquel; Simonis, Fabienne D.; Gordo-Vidal, Federico; Suarez, David; Schultz, Marcus J.; et al. (Frontiers in Medicine, 2023)
There is no consensus on whether invasive ventilation should use low tidal volumes (VT) to prevent lung complications in patients at risk of acute respiratory distress syndrome (ARDS). The purpose of this study is to determine if a low VT strategy is more effective than an intermediate VT strategy in preventing pulmonary complications. A randomized clinical trial was conducted in invasively ventilated patients with a Lung Injury Prediction Score (LIPS) > 4 performed in the intensive care units of ten hospitals in Spain and one in the United States of America (USA) from November 3, 2014 till August 30, 2016. Patients were randomized to invasive ventilation using low VT (≤ 6 ml/kg predicted body weight, PBW) (N = 50) or intermediate VT (> 8 ml/kg PBW) (N = 48). The primary endpoint was development of ARDS during the first 7 days after initiation of invasive ventilation. Secondary endpoints included development of pneumonia and severe atelectases; length of Intensive Care Unit (ICU) and hospital stay; and ICU, hospital, 28– and 90–day mortality. In total, 98 patients [67.3% male], with a median age of 65.5 years [interquartile range 55–73], were enrolled until the study was prematurely stopped because of slow recruitment and loss of equipoise caused by recent study reports. At day 7, 5 (11.9%) patients in the low VT group, and 4 (9.1%) patients in the intermediate VT group had developed ARDS (risk ratio, 1.16 [95% CI, 0.62–2.17]; P=0.735). The incidence of pneumonia and severe atelectasis was also not different between the two groups. Use of a low VT strategy did neither affect length of ICU and hospital stay nor mortality rates. In patients at risk for ARDS, a low VT strategy did not result in a lower incidence of ARDS than an intermediate VT strategy.